Formulation and implementation of a software on armed concrete stairs systems in Civil Engineering projects - Alvarez Ruffrán, Jorge Enrique (2019)
The little regulation existing in our country regarding construction highlights the fact of the existence of a great deficiency in the design as in the execution of the same. One of the affected components and the one dealt with in this article are the reinforced concrete stairway systems, systems that are not very valued but are of vital importance in a building, which present a design flaw due to various factors, for which purpose a software that analyzes and designs various systems of reinforced concrete stairs in order to implement it in various projects. Achieving the realization of it and concluding a favorable impact on Civil Engineering.